Patterns Of Intra-Operative Opioid Dosing By Anaesthesiologist; Do They Reflect Patient’s Analgesic Need? - Tang, M.Y. (Malaysian Society of Anaesthesiologists, 2017)
While it is recommended to employ multimodal analgesic techniques whenever possible, often strong opioids remain the mainstay of perioperative analgesics. We conducted a pilot observation study to look into patterns and factors affecting intraoperative opioid dosing by anaesthesiologists, and compared that to postoperative opioid dosing by adult patients. We found that intraoperative opioid dosing by anaesthesiologists was not associated with patient’s weight, gender nor the types of surgery. The age of the patient was weakly associated with intraoperative opioid dosing by the anaesthesiologist at a regression coefficient of -0.091 (95%CI -0.181, -0.001), p=0.048. Within the first six hours postoperatively, 33% of patients from spine surgery group actually dosed themselves more than what the anaesthesiologist did intraoperatively, 21.4% for peripheral limb surgery group and 3.2% in abdominal surgery group. Our study highlighted the possibility of under-dosing of opioids by anaesthesiologists in these subgroups and failure to apply multimodal analgesia in our daily anaesthetic care.